AMELIORATING TOMATO PRODUCTIVITY AND WATER-USE EFFICIENCY UNDER WATER SALINITY - M. N. Feleafel; Z. M. Mirdad (Journal of Animal and Plant Sciences, 2014)
Salinity affects plant growth and productivity through its osmotic effect, a toxicity of salt ions, and changes in soil physical and chemical properties. This work aims to accelerate root development, hence increasing the plant's ability to absorb more nutrients from the soil in order to avoid the deleterious effects of salinity though using starter solutions and humic acid. Four starter solutions (SS); SS1: control, SS2: 200-200-200 (1:1:1), SS3: 150-300-150 (1:2:1) and SS4: 100-400-100 (1:4:1) mg l-1 of  N-P2O5-K2O and three rates of humic acid (HA); 0, 750 and 1500 mg l-1, as well as their interactions, were studied on tomato plants irrigated with saline water (EC = 3.8). Tomato plants receiving SS3 recorded highest mean values of leaf area, root and stem dry matter, fruit mass (161.8 g), fruit yield ha-1 (115.5 ton ha-1), and water use efficiency (16.0 kg m-3), as well as caused a reduction in fruit quality (firmness, total soluble solid , dry matter, pH, and the EC. While, tomato plants receiving SS4 achieved the highest leaf and total dry matter per plant, the number of fruit clusters per plant(6.7), the percentage of fruit yield in 1-2 picks (59.9%), fruit dry matter and fruit EC. Increasing HA rate up to 1500 mg l-1 led to significantly increased leaf area, total dry matter, number of fruits per plant(37.3), fruit mass (138.3 g), yield ha-1 (103.0 ton ha-1) and WUE (14.3 kg m-3) traits compared to control treatment. However, application of HA at rate 750 mg l-1 gave the highest mean values of stem dry matter, fruit number clusters per plant, and fruit firmness. Dual application of SS3 with HA at 750 mg l-1 achieved the best results in alleviating the deleterious effects of salinity stress on tomato plants. This was evidenced by maximum leaf area, fruit number clusters per plant (7.2), fruit mass (180.3 g), fruit yield (140.63 ton ha-1), and WUE (19.5 kg m-3). While application of SS2 + HA at 1500 mg l-1 was shown to be suitable for improving tomato fruit quality.
Keywords: NPK starter; humic; dry matter accumulation; yield; fruit quality; yield pattern